IDENTIFIKASI SITUASI BERISIKO BAGI PENGENDARA SEPEDA MOTOR DI DAERAH ISTIMEWA YOGYAKARTA DENGAN PENDEKATAN NATURALISTIC DRIVING STUDY - Annisa Rahmatillah, Aulia
In 2022, Indonesia recorded as many as 139,258 traffic accidents resulting in a total of 201,944 victims. The majority of traffic accidents, about 77%, involved motorcycles with 40% of the drivers aged 25-40 years. In the Special Region of Yogyakarta, during the period from 2018 to 2021, out of a total of 36,881 traffic accident victims, as many as 29,722 victims or about 80.59% were victims of accidents involving motorcycles. This research provides an overview of the risky situations that motorcycle riders in the Special Region of Yogyakarta might face using the naturalistic driving study (NDS) method. Data collection involved 14 female participants who reside in the Special Region of Yogyakarta and ride motorcycles for 1-2 days. Participants drove motorcycles equipped with a camera facing the road to record situations and conditions during the trip. Video recordings were processed through data reduction to produce categories of risky situations or safety critical events (SCE). The severity of each category of risky situations was assessed based on the assessment of 5 respondents who have more than 10 years of experience riding motorcycles. Using the severity assessment results and the number of risky situations, each category was mapped into a severity-frequency matrix to determine the risk level of each category. This study resulted in 755 dangerous situations that might be experienced by female motorcyclists in the Special Region of Yogyakarta, which were divided into 29 categories. Of these 29 categories, 8 have a very high risk level, 14 have a high risk level, and 7 categories have a moderate risk level. To reduce the risk in the 8 categories with a very high risk level, recommendations were made using the engineering, education, and enforcement (3E) framework.